2015
DOI: 10.1186/s12893-015-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open wedge resection for gastrointestinal stromal tumors of the stomach: a single-center 8-year retrospective cohort study of 156 patients with long-term follow-up

Abstract: BackgroundThe aim of this study was to compared laparoscopic (LWR) and open wedge resection (OWR) for the treatment of gastric gastrointestinal stromal tumors (GISTs).MethodsThe data of 156 consecutive GISTs patients underwent LWR or OWR between January 2006 and December 2013 were collected retrospectively. The surgical outcomes and the long-term survival rates were compared. Besides, a rapid systematic review and meta-analysis were conducted.ResultsClinicopathological characteristics of the patients were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
(76 reference statements)
3
25
1
Order By: Relevance
“…In addition, open surgery results in large surgery trauma, delayed recovery, and serious postoperative complication. As reported, the overall complication rate including anastomotic hemorrhage, delayed gastric emptying, and abdominal abscess was as high as 12.1 % [21]. The open surgery-related complications adversely affect the patient's quality of life postoperatively.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, open surgery results in large surgery trauma, delayed recovery, and serious postoperative complication. As reported, the overall complication rate including anastomotic hemorrhage, delayed gastric emptying, and abdominal abscess was as high as 12.1 % [21]. The open surgery-related complications adversely affect the patient's quality of life postoperatively.…”
Section: Discussionmentioning
confidence: 91%
“…According to available data from the literature, about 40% of patients underwent laparoscopic surgery, and this fact reduced the postoperative morbid-ity. The reduction of the postoperative pain and blood loss, faster start of oral intake, and a better esthetic effect are some of the advantages of this minimally invasive technique [14,15]. Data from the literature showed no significant difference in the five-year survival percentage between laparoscopic wedge resection and open wedge resection treated GIST patients (93.7% for the first, and 95.5% for the second group) [16].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several large case-control studies have reported on the outcomes of laparoscopic resection of gastric GIST in comparison with conventional open resection. Tables 1-3 summarizes the results from several of these large (n>50) case-control studies demonstrating that laparoscopic resection can be performed with a low conversion rate and was associated with superior perioperative outcomes such as shorter hospital stay, earlier oral intake, lower morbidity with similar oncological outcomes compared to the open approach (27)(28)(29)(30)(31)(32). Similarly, several systematic reviews and meta-analyses have demonstrated that laparoscopic resection was superior in perioperative outcomes compared to open surgery (33)(34)(35).…”
Section: Comparison Between Laparoscopic Versus Open Resection For Gistsmentioning
confidence: 99%